A Pilot Study of Obesogenic Eating Behaviors in Children With Migraine. (June 2016) - Ray, Stephen; Singh, Shashi Bhushan; Halford, Jason C. G.; Harrold, Joanne A.; Kumar, Ram
We studied associations between migraine severity and obesogenic eating behaviors in children with a prospective cross-sectional, clinic-based study. Migraine severity was quantified using the PedMIDAS tool and attack frequency. Eating behaviors were assessed using the Dutch Eating Behaviour Questionnaire and the Child Eating Behaviour Questionnaire. Food intake was assessed using a Food Intake Questionnaire. Statistical tests of association between eating behavior, food intake, and adiposity with migraine severity were performed. Sixty children (mean age = 10.9 years, standard deviation = 3.1; 26 males) were recruited. There was a positive correlation between the Child Eating Behaviour Questionnaire desire to drink subscale and PedMIDAS scores (r = 0.41, P = .01). Attack frequency was associated with higher intake of high fat or sugar content food and drink (r = 0.27, P = .04). No association between migraine severity and adiposity was found. Suggestion that migraine severity in children is associated with certain obesogenic eating behaviors requires further large study investigation.